2020
DOI: 10.3389/fonc.2020.01216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Impact of Concomitant Mutations in Anaplastic Lymphoma Kinase Rearrangement Advanced Non-small-Cell Lung Cancer (Guangdong Association of Thoracic Oncology Study 1055)

Abstract: Background: In patients with anaplastic lymphoma kinase (ALK) rearrangement-positive advanced non-small-cell lung cancer (NSCLC), ALK inhibitors are now the standard treatment, but their clinical efficacy varies widely for each patient. In this multicenter retrospective study, we evaluated the clinical efficacy of crizotinib according to the ALK rearrangement variants and concomitant mutations present. Patients and Methods: A total 132 patients with ALK rearrangement advanced NSCLC from 4 centers in Guangdong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Besides, in our study, NGS identified TP53 mutations to be the most common type of concomitant mutation with ALK rearrangement, with an incidence of 24%, which was comparable to the 20-29% reported by other investigators (1,41). In addition to identifying the mutations concomitant with ALK rearrangement, we also analyzed the relationships of these combinations with prognosis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Besides, in our study, NGS identified TP53 mutations to be the most common type of concomitant mutation with ALK rearrangement, with an incidence of 24%, which was comparable to the 20-29% reported by other investigators (1,41). In addition to identifying the mutations concomitant with ALK rearrangement, we also analyzed the relationships of these combinations with prognosis.…”
Section: Discussionsupporting
confidence: 84%
“…Lung cancer remains the most common malignancy worldwide, the morbidity and mortality of which are at the forefront of global research (1). With the recent development in targeted therapy, treatment for patients with non-small cell lung cancer (NSCLC) has changed substantially (2).…”
Section: Introductionmentioning
confidence: 99%
“…Li and coworkers reported in 132 NSCLC patients with ALK rearrangement a frequency of 0.76% of KRAS mutations and 2.3% of EGFR mutations. 19 The fundamental role of EML4-ALK fusion gene in the pathogenesis of ALK-rearranged LUADs was directly supported through the study of transgenic mouse lines that express EML4-ALK specifically in lung alveolar epithelial cells: all these transgenic mice developed adenocarcinoma nodules in lungs a few weeks after birth. 20 These tumors were exquisitely sensitive to ALK-TKIs.…”
Section: Alk-rearranged Luadmentioning
confidence: 99%
“…Lung cancer is one of the most frequently diagnosed cancers around the world. [1][2][3][4] It is also the leading cause of highest mortality and morbidity in such patients. [5][6][7][8] Surgery is recommended for lung cancer as one of the most effective management.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most frequently diagnosed cancers around the world [1–4] . It is also the leading cause of highest mortality and morbidity in such patients [5–8] .…”
Section: Introductionmentioning
confidence: 99%